Experimental and Microscopic Analysis for Impact of Compaction Coefficient on Plastic Strain Characteristic of Soft Clay in Seasonally Frozen Soil Regions - Miaomiao Sun; Zhanggong Huang; Zouying Liu; Ganggui Liu; Chengbao Hu; Jiaying Liu (Fractal and Fractional, 2025)
Freeze–thaw cycles and the soil compaction coefficient (λc) have significant influence on the plastic strain for the foundation of underground structures in seasonal permafrost regions. Understanding the microstructural evolution of freeze–thawed soil is pivotal for assessing the long-term settlement of infrastructure foundation under repeated train loading. This study investigates the impacts of freeze–thaw cycles and λc on the plastic strain and pore size distribution (PSD), as well as fractal characteristics, of soft clay via a set of cyclic triaxial tests and nuclear magnetic resonance (NMR) analyses. Fractal theory was adopted to analyze the heterogeneity of soil specimens. The results showed that an increase in λc could efficiently alleviate the cumulative plastic strain. It also decreased the proportion of large pores and facilitated the generation of small and medium-sized pores. The analysis of the NMR test demonstrated that the freeze–thaw cycle led to the disruption of the soil’s microporous structure. Moreover, a higher value of λc encouraged the formation of a more intricate and uniform pore structure. This, in turn, increased the fractal dimension, enhanced the structural heterogeneity, and thereby improved the soil’s structural complexity and its resistance to deformation. These findings underscore the significance of achieving optimal compaction levels to bolster soil stability under freeze–thaw conditions, provide valuable guidance for infrastructure design in permafrost regions, and help to ensure the durability and stability of transportation networks, such as railways and roads, over time.